1995
DOI: 10.1079/bjn19950102
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro procedure for studying enzymic dephosphorylation of phytate in maize-soyabean feeds for turkey poults

Abstract: An in vitro method was developed to predict inorganic P release from maize-soyabean poultry feeds containing supplemental phytase (EC 3.1.3.8), and to quantify the effect of acid phosphatase (EC 3.1.3.2), fungal protease (EC 3.4.23.6) and Aspergillus niger cellulase (EC 3.2.1.4) on phytate dephosphorylation. Pepsin (EC 3.4.23.1) and panmatin digestion periods were preceded by a 30 min pre-incubation at pH 525 to simulate digestion in the crop of poultry. Pancreatin digestion was carried out in dialysis tubing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…Among these organic acids, citric acid (CA), due to its unique flavor and high buffering capacity, has been extensively used for diet acidification (Hossain et al, 2007). Its efficacy to dephosphorylate the phytate in vitro has also been reported (Zyla et al, 1995). Citric acid supplementation resulted in improved P contents in the scute of Huso huso fed on plant meal based diet (Khajepour and Hosseini, 2011;.…”
Section: Introductionmentioning
confidence: 97%
“…Among these organic acids, citric acid (CA), due to its unique flavor and high buffering capacity, has been extensively used for diet acidification (Hossain et al, 2007). Its efficacy to dephosphorylate the phytate in vitro has also been reported (Zyla et al, 1995). Citric acid supplementation resulted in improved P contents in the scute of Huso huso fed on plant meal based diet (Khajepour and Hosseini, 2011;.…”
Section: Introductionmentioning
confidence: 97%
“…In vitro digestion of the diets was performed according to previously published methods (Bedford & Classen, 1993;Zyla et al 1995), with minor modifications. All in vitro digestion steps were carried out at 40°C to simulate more closely avian body temperature, using a waterjacketed incubator (Forma Scientific Inc., Marietta, OH, USA) customized with bars that rotated the tubes horizontally at 19 r.p.m.…”
Section: Digestionmentioning
confidence: 99%
“…Using citric acid has increased phytate dephosphorylation in vitro (Zyla et al 1995) and increased phytate-P utilization in broilers diet and reduced available P requirement by about 0.10% (Boling et al 2001). Esmaeilipour et al (2011) observed that citric acid supplementation to wheat-soybean meal-based diet (low in P) increases the P retention in broilers.…”
Section: Introductionmentioning
confidence: 99%